Hubungan Kualitas Pelayanan Terhadap Kepuasan Pasien di Puskesmas Rappang - Adri, Khaeriyah (Jurnal Ilmiah Kesehatan Delima, 2025)
This study aims to explore the relationship between service quality and patient satisfaction at the Rappang Health Center. The research method used is quantitative with a cross-sectional approach, namely research to study the dynamics of the correlation between independent variables and the dependent variable by means of observational approaches or data collection using questionnaires. The results showed that there was a significant relationship between the empathy dimension in service quality and patient satisfaction. This study emphasizes the importance of improving the quality of health services to increase patient satisfaction. Other factors such as tangibility, reliability, responsiveness and assurance can also influence patient satisfaction. This research was conducted at the Rappang Health Center, Sidrap Regency, with a population of patients seeking treatment in July 2023. The study sample was 100 people. Data was collected using a questionnaire and analyzed using statistical methods. The results of the analysis show that the majority of respondents give a good assessment of service quality in all dimensions. This study provides recommendations to the Rappang Health Center to continue to improve service quality in order to increase patient satisfaction.